Keterampilan Kepemimpinan Perempuan Dalam Kajian Historis Islam - Sarah Rifat Alhawari; Imas Kania Rahman; Amir Tengku Ramly (Universitas Ibn Khaldun Bogor, 2021)
The emergence of various understandings around women who present new figures makes it seem as if they have lost the figure of Qudwah for Muslim women. All the roles that Islam has given to women, require them to have some special skills related to Islamic leadership. The roles will affect themselves, their families, and the communities. This study aims to revive the figure of Muslim women in the study of Islamic history in order to fill the Qudwah void in women these days. By doing this study, it is hoped that women will understand more about the nature and role of women in Islam. This research is a library research method which the researcher tries to study the related literature. This study succeeded in revealing the figure of women in Islamic History who were able to apply leadership skills without getting out of context of being a woman; which will be useful for character development for the woman herself.